MEMBERSHIP TO THE OECD AS AN INSTRUMENT FOR THE UNIVERSALIZATION OF EDUCATION IN BRAZIL: A CONSTITUTIONAL ANALYSIS (Reflection and Critique Law Magazine, 2026)
Education is a fundamental right guaranteed by the 1988 Federal Constitution and reaffirmed by international instruments such as the Universal Declaration of Human Rights. The UN 2030 Agenda, through SDG 4, aims to ensure inclusive, equitable and quality education. This article examines how Brazil’s accession to the Organization for Economic Co-operation and Development (OECD) can contribute to the realization of this right, based on bibliographic and documentary review and comparative analysis of educational policies. The results indicate that OECD integration can strengthen Brazil’s educational system by adopting successful practices already consolidated in member countries, such as innovative curricula, teacher appreciation, efficient evaluation mechanisms and sustainable financing. These measures may help the country move closer to achieving SDG 4 and reinforce its constitutional commitment to universal education. However, the study also reveals limitations. Regional inequalities, budgetary restrictions, institutional resistance and the risk of excessive dependence on international parameters are relevant challenges. It is concluded that OECD accession should be seen as a strategic opportunity for international cooperation, but not as an automatic solution. Its success will depend on Brazil’s ability to adapt global standards to its social and federative context, transforming formal commitments into concrete results to ensure quality education.